Effect of 12 weeks of once-daily tiotropium/olodaterol on exercise endurance during constant work-rate cycling and endurance shuttle walking in chronic obstructive pulmonary disease. (6th February 2018) - Maltais, François; O'Donnell, Denis; Gáldiz Iturri, Juan Bautista; Kirsten, Anne-Marie; Singh, Dave; Hamilton, Alan; Tetzlaff, Kay; Zhao, Yihua; Casaburi, Richard
Background: The TORRACTO ® study evaluated the effects of tiotropium/olodaterol versus placebo on endurance time during constant work-rate cycling and constant speed shuttle walking in patients with chronic obstructive pulmonary disease (COPD) after 12 weeks of treatment. Methods: The effects of once-daily tiotropium/olodaterol (2.5/5 and 5/5 μg) on endurance time during constant work-rate cycle ergometry (CWRCE) after 6 and 12 weeks of treatment were compared with placebo in patients with COPD in a randomized, double-blind, placebo-controlled, parallel-group clinical trial. Endurance time during the endurance shuttle walk test (ESWT) after 6 and 12 weeks of treatment was also evaluated in a subset of patients. Results: A total of 404 patients received treatment, with 165 participating in the ESWT substudy. A statistically significant improvement in endurance time during CWRCE was observed after 12 weeks (primary endpoint) with tiotropium/olodaterol 5/5 µg [14% ( p = 0.02)] but not with tiotropium/olodaterol 2.5/5 µg [9% ( p = 0.14)] versus placebo. In the ESWT substudy, a trend to improvement in endurance time during ESWT after 12 weeks (key secondary endpoint) was observed with tiotropium/olodaterol 5/5 µg [21% ( p = 0.055)] and tiotropium/olodaterol 2.5/5 µg [21% ( p = 0.056)] versus placebo. Conclusion: Tiotropium/olodaterol 5/5 µg improved endurance time during cycle ergometry versus placebo, with a strong tendency to also improve walking endurance time. [ClinicalTrials.gov identifier: NCT01525615.]